PENGEMBANGAN DAN PELATIHAN SIPsiMas (SISTEM INFORMASI PELAYANAN ADMINISTRASI MASYARAKAT) DI KECAMATAN SIDOMUKTI SALATIGA - Purwati, Heni; Wiyaka; Arisul Ulumuddin; Bambang Agus Herlambang; Rizky Esti Utami (Universitas PGRI Yogyakarta, 2025)
Population administration and correspondence services at the village and sub-district levels often present obstacles for the community, especially since they must come directly to the office to handle various needs. In an effort to overcome this problem, the community service team sought to develop sipsidomukti on SIPsiMas (Community Administration Service Information System), which is a digital-based system that allows to community of Sidomukti sub-district, Salatiga City, to process documents online. The program aims to improve the efficiency of administrative services, reduce queues at village and sub-district offices, and provide easy access for the community without time and place restrictions. The system development is carried out using web-based technology and mobile applications that allow residents to submit, monitor, and print documents independently. The program implementation methods include: needs analysis, design and development, outreach and training, and evaluation and improvement. With the existence of sipsidomukti in SIPsiMas, administrative services in Sidomukti sub-district have become faster, more transparent, and more efficient, increasing public satisfaction with public services. Keywords: SIPsiMas, public service, digitalization, administration, Sidomukti District